Adverse events following immunization of mRNA-1273 (Moderna) booster vaccine in clerkship students - Hendarto, Hari; Akbar, Femmy Nurul; Nasir, Narila Mutia; Wulandari, Endah; Adlani, Hadianti (International Journal of Public Health Science (IJPHS), 2024)
Two-dose primary vaccine administration was the best strategy to reduce the prevalence and severity of COVID-19. Improved immunity and antibody response to the new variant virus by administering a booster vaccine is needed. Health workers are the main priority for administering the mRNA-1273 (Moderna) booster vaccination in Indonesia. This vaccine has high effectiveness, and safety, however, data and evaluation of adverse events following immunization (AEFI) is required. This study aimed to determine the AEFIs of mRNA-1273 booster vaccination in clinical clerkship students as an early adult age group. The research design was a repeated cross-sectional study using purposive sampling technique. There were 214 subjects who met the requirements. Subject filled out an online questionnaire containing evaluation of AEFIs. The most local AEFIs symptoms were pain at the injection site (79.0%), while the common systemic symptoms were headache, drowsiness, weakness, and fever (37.4%; 26.2%; 9.8%; 9.3%). Most AEFIs were felt within 30 minutes to three days. No respondents required hospitalization, experienced anaphylactic shock, became disabled, or died. The AEFIs did not have a significant relationship with gender, history of allergies, co-morbidities, or history of COVID-19. This information is used as a preventive or educational effort to support implementation vaccine in Indonesia.